Prevalence and independent predictors of Iron deficiency in Yemeni patients with congestive heart failure: a retrospective cross-sectional study - Mohammed Abdullah; Basheer Abdo; Faisal Ahmed; Khaled Alzanen; Nabile Albadani; Mohamed Badheeb (Scientific Reports)
Abstract Heart failure (HF) constitutes a substantial burden on healthcare systems worldwide, contributing to elevated rates of mortality and morbidity. Iron deficiency (ID), both with and without concurrent anemia, has been identified in up to half of all patients with CHF and is associated with an increased risk of HF exacerbations, higher rates of hospitalization, and diminished quality of life. However, data from resource-limited settings remain limited. In this study, we reviewed 108 adult Yemeni patients with HF who also had concomitant ID, defined as serum ferritin concentrations of < 100 ng/mL or 100–299 ng/mL with transferrin saturation < 20%. The prevalence of ID among HF patients was determined, and independent predictors of ID were assessed using univariate and multivariate regression analyses. Anemia was present in 64 (59.3%), ID was observed in 65 (60.2%), and both anemia and ID were concurrently present in 44 (40.7%) patients. The mean ejection fraction among the study cohort was 34.2 ± 6.3%. Multivariate regression analysis identified New York Heart Association class III (OR: 4.46; 95% CI: 1.65–12.90, p = 0.004), presence of anemia (OR: 3.95; 95% CI: 1.51–11.23, p = 0.007), and an EF < 30% (OR: 9.42; 95% CI: 1.97–54.64, p = 0.007) as independent predictors of ID. These findings highlight the potential under-recognition of ID in patients with congestive HF, suggesting the need for routine assessment of iron status in this patient population.